Single-Cell View of Carbon and Nitrogen Acquisition in the Mixotrophic Alga Prymnesium parvum (Haptophyta) Inferred From Stable Isotope Tracers and NanoSIMS - Carpenter, Kevin J.; Bose, Maitrayee; Polerecky, Lubos; Lie, Alle A. Y.; Heidelberg, Karla B.; Caron, David A. (Frontiers in Marine Science, 2018)
Nutritional modes of unicellular eukaryotes range from pure photoautotrophy of some phytoplankton to pure heterotrophy of species typically called protozoa. Between these two extremes lies a functional continuum of nutrient and energy acquisition modes termed mixotrophy. Prymnesium parvum is an ecologically important mixotrophic haptophyte alga that can produce toxins and form ecosystem disruptive blooms that result in fish kills and changes in planktonic food web structure. We investigated carbon and nitrogen acquisition strategies of single cells of P. parvum using a combined experimental-imaging approach employing labeling of live cells with stable isotope tracers (13C and 15N) followed by measurement of cellular isotopic ratios using nanometer-scale secondary ion mass spectrometry (NanoSIMS). With this method, we were able to quantify the relative contributions of photosynthesis and heterotrophy to the nutrition of the alga. Our results suggest that P. parvum relies on predation primarily for nitrogen, while most carbon for cellular building blocks is obtained from inorganic sources. Our analysis further revealed that nitrogen assimilation can vary up to an order of magnitude among individual cells, a finding that would be difficult to determine using other methods. These results help to improve our understanding of mixotrophy across the enormous diversity of eukaryotes, one cell and one species at a time.